2020
DOI: 10.1101/2020.04.30.20085928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in breast cancer patients: a cohort at the Institut Curie hospitals in the Paris area

Abstract: Background: Cancer patients have been reported to be at higher risk of COVID-19 complications and deaths. We report the characteristics and outcome of patients diagnosed with COVID-19 during breast cancer treatment at Institut Curie hospitals (ICH, Paris area, France).Methods: An IRB-approved prospective registry was set up at ICH on March 13 th , 2020 for all breast cancer patients with COVID-19 symptoms or radiologic signs. Registered data included patient history, tumor characteristics and treatments, COVID… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
3
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 14 publications
7
74
3
6
Order By: Relevance
“…Noteworthy, in Vuagnat's study, univariate analysis showed that the ongoing cancer therapy (within 30 days) was not associated with disease severity, and there were no further analysis into cancer therapy within 7 or 14 days. Besides, the number of patient events in their study was too small to have multivariate analysis [14]. In addition, our study demonstrated the age over 75 as a distinct risk factor of severity, which shared a similar results with Vuagnat's report (age over 70).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Noteworthy, in Vuagnat's study, univariate analysis showed that the ongoing cancer therapy (within 30 days) was not associated with disease severity, and there were no further analysis into cancer therapy within 7 or 14 days. Besides, the number of patient events in their study was too small to have multivariate analysis [14]. In addition, our study demonstrated the age over 75 as a distinct risk factor of severity, which shared a similar results with Vuagnat's report (age over 70).…”
Section: Discussionsupporting
confidence: 89%
“…Remarkably, breast cancer patients with COVID-19 had lower disease severity and mortality when compared with general cancer patients. Compared with the similar works of breast cancer patients with COVID-19 in the world, the mortality in our study was 6.7%, which is similar to that in Vuagnat's study(6.7%) and higher than Kalinsky's study(3.7%) [14,18]. These different outcomes among breast cancer patients could be explain by the different regional distribution and availability of medical cure, testing methods, subtypes and virulence of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Following initial database search and screening, twenty-eight full-text articles were assessed for eligibility. Among these studies, twelve studies were excluded because individual patient data required for calculation of case fatalities in our study-specified treatment modality groups were not reported [8][9][10][11][12][13][14][15][16][17][18]. Among these studies, because of overlapping data of four patients with Garassino et al, Stroppa et al was excluded from the analysis [19].…”
Section: Study Characteristics and Definitionsmentioning
confidence: 99%
“…Routine delay or discontinuation of antineoplastic therapy in patients without suspected/confirmed SARS-CoV-2 infection is not recommended even in times of pandemic (DII u ). 18 , 20 , 31 , 33 , 40 , 92 , 93 , 94 In case of suspected SARS-CoV-2 infection, e.g. due to contact with a confirmed case or a high incidence in the area, we strongly recommend to quarantine the patient and delay antineoplastic therapy for up to 14 days, if not detrimental for cancer prognosis (AIII).…”
Section: Management Of Cancer Carementioning
confidence: 99%